MUSEUM TANAH DAN PERTANIAN SEBAGAI SUMBER BELAJAR SEJARAH LINGKUNGAN DAN MEDIA MENUMBUHKAN KESADARAN LINGKUNGAN - Santosa, Yusuf Budi Prasetya; Dasfordate, Aksilas; Setiyonugroho, Ponco (Universitas Negeri Malang, 2025)
The Museum Tanah dan Pertanian is one of the museums located in the city of Bogor. The Museum of land and agriculture can be used as a learning resource for environmental history because it has a variety of collections related to land and agriculture in Indonesia, which includes the dimensions of history, environment, politics, technology, and the future of Indonesian Agriculture. This study uses qualitative research methods with library research approach. The result of this study is the Museum Tanah dan Pertanian can be used as a source of learning history, because the various collections owned by the museum can be associated with the scope of environmental history, among others 1) the natural environment in the past, 2) modes of production, 3) the perception of ideology and cultural values and 4) public responses that arise in the form of debates, laws and political regulations related to the environment. Various information obtained from the museum is converted into knowledge, which will foster environmental awareness